Analisis Kesesuaian Investasi Saham Syariah pada Aplikasi Indo Premier Sekuritas - Ghaisani, Sabila Nur; Susilawati, Cucu (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2025)
Background: The number of users of sharia stock investment in Indonesia is increasing. Likewise, there are various investment applications, and almost all have a Sharia scheme. Research Objectives: To determine the suitability of sharia in implementing sharia investment in the Indo Premier Sekuritas Application. Methods: This study uses a qualitative approach with a descriptive method. Data sources are primary and secondary data. Data collection techniques are observation, interviews, documentation, and literature studies. Results: Present a summary of the main findings of the study, including the primary data, trends, or patterns found.. Conclusion: Sharia stock investment in the Indo Premier Sekuritas Application uses multiple contracts, including the bai' al-musawamah contract, the mudharabah contract, and the ijarah contract. This type of multi-contract in Sharia economic law is called al-uqud al-murakkabah al-mutajanisah. This means that the contracts are similar and may be combined. In addition, the Sharia stock portfolio in the Indo Premier Sekuritas Application is in accordance with Sharia provisions.